The Burden of Menstrual Migraine: Advances in diagnosis, treatment, and understanding of pathogenesis - Głogowska, Paulina; Furtak, Daria; Tulej, Dawid; Dziedzic, Alicja; Grela, Wiktor; Niewiadomska, Jagoda; Marko, Natalia; Gniaź, Natalia; Marciniuk, Dominika; Górska, Aleksandra (Journal of Education, Health and Sport, 2025)
Menstrual migraine is a debilitating neurological condition linked to hormonal fluctuations during the menstrual cycle. It disproportionately affects women of reproductive age, imposing significant personal and societal burdens. Characterized by intense, prolonged headaches often resistant to standard treatments, menstrual migraines are primarily triggered by estrogen withdrawal and further influenced by prostaglandins and neurotransmitter dysregulation. This review synthesizes current knowledge on the pathophysiology of menstrual migraine, emphasizing hormonal and genetic factors, and highlights diagnostic criteria distinguishing pure menstrual migraine from menstrually related migraine. The review examines both acute and chronic treatment approaches. Pharmacological options such as triptans, NSAIDs, and the emerging use of CGRP inhibitors and lasmiditan show varying levels of efficacy, while hormonal therapies aim to stabilize estrogen fluctuations. Non-pharmacological strategies, including lifestyle modifications, cognitive-behavioral therapy, and acupuncture, offer complementary relief and improve quality of life. Despite advancements, significant challenges remain, including variability in treatment response and a lack of biomarkers for precise diagnosis and management. Furthermore, this review highlights gaps in current research, such as the need to better understand hormonal sensitivity and long-term treatment safety. Future directions emphasize the development of personalized therapies, innovative diagnostic tools, and more inclusive studies addressing the socioeconomic burden of menstrual migraines. By bridging these gaps, the medical community can advance care for affected women, reducing disability and improving overall well-being.